Updating and Extending Indicative Budget Standards for Older Australians: Final Report - Saunders, Peter; Patulny, Roger; Lee, Adeline (UNSW Sydney, 2004)
This report provides estimates of a new comfortably affluent but sustainable (CAS) budget standard for older Australians. The CAS standard reflects a standard of living among older, healthy and fully active self-funded retired Australian that allows them to engage actively with a broad range of leisure and recreational activities without having to require a rapid or substantial disbursement of assets. It represents a lifestyle that is common amongst those in the top (income) quintile of the aged population. A budget standard estimates what is needed to attain a specific standard by a particular household living in a particular place at a particular time. This involves specifying the items required to achieve the standard and pricing them to arrive at the income level that would support the necessary level of consumption. Budget standards incorporate expert assessments of the level of consumption of goods and services and participation in different activities that can be supported by a given level of income. Among their many uses, budget standards can be used to benchmark the adequacy of government income support payments and the relativities between payments for different families.
SPRC Report 2/04